MODEL OF HOSPITAL INFORMATION SYSTEM ACCEPTANCE IN HOSPITALS OWNED BY THE SOCIAL SECURITY ORGANIZATION - Abolhassan Pourhosseini, Seyed; Reza Kasraei, Ahmad; Sohrabi, Tahmorth (Humanities & Social Sciences Reviews, 2021)
Purpose: The purpose of this study is to provide a model of hospital information system acceptance owned by the Social Security Organization. Methodology: This study was performed Cross-sectional â€“ applied and descriptively and analytically. This study had two stages. The study population was in the first stage (qualitative), information technology experts in the Social Security Organization (6 people) and the second stage (quantitative), users of the hospital information system in medical centres owned by the Social Security Organization (375 people). The first stage of this study was based on interviews with IT experts. The second stage of the study was based on the results of interviews with experts using the design of a researcher-made questionnaire. The validity of the questionnaire was measured by using the opinion of experts in the field of information technology and health information technology and by calculating the CVR index. Cronbach’s alpha coefficient (0.941) was used to assess the reliability of the questionnaire. The questionnaire consisted of 12 axis and 46 questions with a five-point Likert scale with a score of 5-1. The interviews were analyzed qualitatively (content analysis) and the questionnaires were analyzed descriptively, analytically (correlation) and structural equation method is done with the help of SPSS software. Main Findings: Evaluation of direct relationships between model factors and hypotheses showed that the relationships between habit with intent to use, intention to use with actual use, increase motivation to use, increase management support, meet user expectations in achieving the expected performance of the system, value the cost to the system and the social impact of co-workers significantly increases the intention to use the system. Also, the coefficient of determination R2 for the target variables, which is the intention of use and actual use, were equal to 0.774 and 0.448, respectively. The goodness of fit (GoF) was equal to 0.671. The study of the effect of demographic factors on the target variables (intention to use and actual use) showed that none of the demographic variables has a significant effect on the intention to use and actual use. By considering these factors, the managers of the Social Security Organization can increase the rate of HIS admission in the hospitals and clinics of this organization. Application of Study: One of the technologies used in the healthcare sector is the hospital information system. It is less developed than other information systems that use information technology and apply quality standards for customer satisfaction. The IT acceptance model is one of the most valid models available that examines the acceptance factors of technology at different levels, including the individual level. Novelty/Originality: The novelty of this research is giving a model of clinic data framework acknowledgement claimed by the Social Security Organization.